Village Apparatus Performance and Public Service Discipline in Pesawahan Village: Kinerja Aparatur Desa dan Disiplin Pelayanan Publik di Desa Pesawahan - Abigil Satria Rifana; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village government plays a central role in delivering administrative public services that directly shape community satisfaction. Specific Background: In Pesawahan Village, Porong District, inconsistencies were observed in task distribution, work discipline, and service timeliness among village apparatus. Knowledge Gap: Previous studies discuss village service quality, yet limited attention is given to how internal discipline, technological ability, and task misalignment simultaneously shape service delivery. Aim: This study describes and analyzes the performance of village apparatus based on work quality, promptness, and responsibility. Results: Findings show that work quality and responsibility are well demonstrated through friendliness, document accuracy, and collaborative task completion, supported by adequate facilities and technological use. However, promptness remains problematic due to irregular attendance, absence of service hour information, and dependence on certain officials for signatures. Novelty: This study reveals how strong service quality can coexist with weak time discipline, creating hidden inefficiencies in village administration. Implications: Strengthening SOP implementation, work discipline, and task alignment is essential for improving administrative reliability at the village level.